STUDENTS’ PERCEPTIONS ON THE USE OF WHATSAPP AS A MOBILE LEARNING PLATFORM IN LEARNING ENGLISH : A Descriptive Research at MA SWASTA DDI CITTA, Soppeng Regency - Irmayanti; Nappu, Syamsiarna; Burhanuddin, Wildhan (Journal of Computer Interaction in Education, 2021)
This research aimed at findings (1) Students’ perceptions on the use of WhatsApp as a mobile learning platform in learning English; (2) The challenges faced by students of Madrasah Aliyah Swasta DDI CITTA in using WhatsApp as a mobile learning platform in learning English. The methodology of this research was descriptive quantitative and qualitative method.The population is 118 students at Madrasah Aliyah Swasta DDI CITTA.The sample consist of 30 students that took randomly at Madrasah Aliyah Swasta DDI CITTA. The instruments used in this research were questionnaire and interview. The findings shows that from 20 items on questionnaire, disagree and strongly disagree has the highest percentage on positive statement. Disagree had a percentage of 30-63% and strongly disagree had a percentage of 26,67-60%.Then, agree and strongly agree had the highest percentage on negative statements. Agree had a of 20-73% and strongly agree had a percentage of of 20-70%. Meanwhile interview results show that there were three challenges faced by students in using WhatsApp as a mobile learning platform namely, students did not understand the material, bad network and internet data. Based on the data obtained, the researcher concludes that students gave negative perceptions on the use of WhatsApp as a mobile learning platform in learning English.